A New Method for Computing The Symmetry of Big Fullerene C180 - Yavari, Morteza; Reza Ashrafi, Ali (Asian Journal of Chemistry, 2010)
It is well known that the symmetry operators in the point group of a molecule always commute with its Hamiltonian operator. So the group H of molecular graph must contain the point group H of the graph. It is also well-known fact that the set of all permutation matrices fixed by Hamiltonian constitute the full automorphism group of the molecular graph under consideration. These facts were used and some new algorithm to compute the symmetry of fullerene C180.